2007
DOI: 10.1002/mats.200700007
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Controlled/Living Radical Polymerization in Emulsified Systems

Abstract: A new MC simulation method is proposed for the controlled/living radical polymerization in a dispersed medium, assuming an ideal miniemulsion system. This tool is used to consider the effects of particle size on the polymerization rates and the molecular weight distributions. For NMP, the polymerization kinetics are basically governed by two conflicting factors, (i) the confined space effect that promotes the coupling reaction between a radical and a trapping agent and (ii) the isolation effect of radicals int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(177 citation statements)
references
References 38 publications
10
166
0
1
Order By: Relevance
“…On the other hand, these two types of models can be discriminated in a straightforward manner by using the miniemulsion polymerization. The IT model leads to show that the polymerization rate increases significantly for D p smaller than ,PXP , while with the SF model the polymerization rate is essentially unchanged with the particle size [9,13,21]. Recently, this simple discrimination method is applied experimentally [22], and concluded that the IT model applies for the dithiobenzoate mediated styrene polymerization.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, these two types of models can be discriminated in a straightforward manner by using the miniemulsion polymerization. The IT model leads to show that the polymerization rate increases significantly for D p smaller than ,PXP , while with the SF model the polymerization rate is essentially unchanged with the particle size [9,13,21]. Recently, this simple discrimination method is applied experimentally [22], and concluded that the IT model applies for the dithiobenzoate mediated styrene polymerization.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, L ν,i is the average number of monomeric units added during a single active period, and therefore, given by: (9) where • is the average active radical period in the ith polymerization locus (particle), which is given by:…”
Section: Polymerization Rate In Dispersed Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO). Tabela 1, estudos teóricos sobre a polimerização RAFT em miniemulsão também já foram publicados [90][91][92][93][94][95][96][97] , contribuindo com a melhor compreensão sobre a cinética de polimerização (e outras características) desse sistema.…”
Section: Polimerização Raft Em Miniemulsãounclassified